Some characteristics of sediments in Cenozoic basins in Northern Vietnam: implication for Oligocene paleoclimate - Mai Thanh, Tan; Dinh Van, Thuan; Le Duc, Luong; Tran Thi Thuy, Van; Ngo Thi, Dao (Vietnam Journal of Earth Sciences, 2024)
Oligocene sediments in northern Vietnam have been extensively studied in terms of geology, stratigraphy, paleogeography, formation environments, tectonics, etc. However, relatively little attention has been paid to the paleoclimate. The Oligocene climate interpreted herein is based on features recorded in sediments taken from the Dong Ho (Hoanh Bo basin), Na Duong (Na Duong basin), and Co Phuc (Red River Trough) formations. These sediments were analyzed using thin-section microscopy, X-ray diffraction, and palynology with the Coexistence Approach. The sediments primarily consist of conglomerate, gritstone, sandstone, siltstone, claystone, and coal shale, deposited in continental environments and dated to the Oligocene based on palynomorph assemblages. The Oligocene paleoclimate is generally warm subtropical, with intermittent hot-humid or cold-dry periods and a slight influence of monsoons. An alternation of hot-humid and cold-dry climates was recorded in the Hoanh Bo basin. In the Red River Trough, the Oligocene climate exhibited a Mean Annual Temperature (MAT) of  9.3-22.2°C and a Mean Annual Precipitation (MAP) of 1122 to 1857 mm, based on the majority of palynological samples, indicating more continental, drier and colder conditions than present. In the Na Duong basin, a warm subtropical climate with a MAT of 9.3-21.7°C and MAP of 1122-1724 mm in the majority of samples was occasionally replaced by hot and humid subtropical periods; the variations in temperature and precipitation followed a similar pattern, suggesting an alternation between dry-cold and humid-hot phases.